Ultraviolet A radiation and COVID‐19 deaths in the USA with replication studies in England and Italy. (31st May 2021) - Cherrie, M.; Clemens, T.; Colandrea, C.; Feng, Z.; Webb, D.J.; Weller, R.B.; Dibben, C.
Summary: Background: Understanding factors impacting deaths from COVID‐19 is of the highest priority. Seasonal variation in environmental meteorological conditions affects the incidence of many infectious diseases and may also affect COVID‐19. Ultraviolet (UV) A (UVA) radiation induces release of cutaneous photolabile nitric oxide (NO) impacting the cardiovascular system and metabolic syndrome, both COVID‐19 risk factors. NO also inhibits the replication of SARS‐CoV2. Objectives: To investigate the relationship between ambient UVA radiation and COVID‐19 deaths. Methods: COVID‐19 deaths at the county level, across the USA, were modelled in a zero‐inflated negative‐binomial model with a random effect for states adjusting for confounding by demographic, socioeconomic and long‐term environmental variables. Only those areas where UVB was too low to induce significant cutaneous vitamin D3 synthesis were modelled. We used satellite‐derived estimates of UVA, UVB and temperature and relative humidity. Replication models were undertaken using comparable data for England and Italy. Results: The mortality rate ratio (MRR) in the USA falls by 29% [95% confidence interval (CI) 40% to 15%) per 100 kJ m –2 increase in mean daily UVA. We replicated this in independent studies in Italy and England and estimate a pooled decline in MRR of 32% (95% CI 48% to 12%) per 100 kJ m –2 across the three studies. Conclusions: Our analysis suggests that higher ambient UVA exposure is associated with lower COVID‐19‐specific mortality. Further research on the mechanism may indicate novel treatments. Optimized UVA exposure may have population health benefits. Abstract : What is already known about this topic? Infectious disease often shows seasonality. Cutaneous production of nitric oxide (NO) following ultraviolet A (UVA) exposure reduces blood pressure, a cardiovascular risk factor. Comorbid cardiovascular disease worsens COVID‐19 outcomes. NO limits SARS‐CoV and SARS‐CoV2 replication in vitro . What does this study add? Higher ambient UVA is associated with lower risk of COVID‐19 death in three countries, when vitamin D synthesis would have been limited. Sun exposure may reduce death from COVID‐19 independently of vitamin D. Linked Comment: R. McKenzie and B. Liley. Br J Dermatol 2021; 185 :246–247 . Plain language summary available online